An overview of Suctorian ciliates (Ciliophora, Suctorea) as epibionts of halacarid mites (Acari, Halacaridae) - Dovgal, Igor; Chatterjee, Tapas; Ingole, Baban (Zootaxa, 2008)
Scant information is available regarding the prevalence and distribution of suctorian ciliates on halacarid mites. However, using this limited information and data from our laboratory on the systematics, biology, ecology and distribution of suctorian ciliates that are epibionts of halacarid mites, we redescribed four suctorian species: Limnoricus ceter (Jankowski), Praethecacineta halacari (Schulz), Thecacineta calix (Schroder) and Acineta sulcata Dons. We also recognized Lissacineta allgeni Jankowski and Thecacineta allgeni (Jankowski) as synonyms of Praethecacineta halacari (Schluz), and Thecacineta laophontis Jankowski and Paracineta moebiusi Kahl as synonyms of Thecacineta calix (Schroder). Many suctorians have been reported, but not properly identified in the halacarid literature. So, we have attempted to identify those suctorians to species level. Lastly, the interactions between the suctorians and their hosts are also discussed and Praethecacineta halacari is also reported for the first time from the Indian coast.